Fungal endocarditis with heart valve replacement and atrial fibrillation posing a treatment challenge: A case report. Issue 48 (25th November 2020) - Zhu, Xiaoxia; Cao, Shugang; Xia, Mingwu; Ding, Chandong; Wang, Rongfeng
Abstract: Rationale: Fungal endocarditis (FE) is a rare disease, in which antifungal treatment is necessary. When FE is complicated with prosthetic heart valve and/or atrial fibrillation, the coadministration of antifungal agents and warfarin is inevitable. We report a case of rheumatic heart disease with atrial fibrillation who developed FE following prosthetic heart valve replacement. The international normalized ratio (INR) increased significantly during the antifungal treatment with fluconazole. A discussion of the antifungal strategy in FE patients with prosthetic heart valves and/or atrial fibrillation and the interaction between antifungal agents and warfarin was performed. Patient concerns: A 54-year-old Chinese woman experienced intermittent fevers, aphemia, and weakness in her right extremities. Her temperature was 38.7°C, and there was atrial fibrillation with heart rate 110 times/min. Neurological examination revealed that she had drowsiness, Broca aphasia, right central facial paralysis, and hemiplegia (Medical Research Council scale, upper limb grade 0, lower limb grade II). Diagnoses: Multiple infarction on magnetic resonance imaging and the occlusion of left middle cerebral artery suggested the occurrence of cerebral embolism. The presence of Candida parapsilosis in the results of 4 blood cultures and the existence of valve vegetation in the reexamination of echocardiogram supported the diagnosis of FE. Interventions: The patient was given antifungal therapy with fluconazol. The INR increased dramatically on the 9th day of antifungal treatment, and subcutaneous bruising occurred at the intravenous infusion site. The antagonist of vitamin K1 was used and warfarin was reduced to a smaller dosage. The antifungal agent was replaced with caspofungin. Outcomes: Her speech improved significantly, and the muscle strength of her paralyzed side reached the Medical Research Council scale of grade IV + . She continued to receive caspofungin for antifungal treatment with relatively stable INR and waited for heart valve surgery. Lessons: The choice of antifungal agents is often a big challenge for FE patients, especially when they need warfarin for anticoagulation. It is better to administer a low dose of warfarin while carefully monitoring the INR or choose the antifungal drugs with little or no effect on warfarin.